Study of limit strains for FCC and BCC sheet metal using polycrystal plasticity - Serenelli, Mariano Javier (2011)
In this research, we analyze forming-limit strains of FCC and BCC materials using a viscoplastic self-consistent polycrystal model (VPSC) in conjunction with the Marciniak?Kuczynski (MK) approach. In particular, our work is focused on the theoretical analysis and comparison between FCC and BCC crystal structures made by Inal et al. [Inal, K., Neale, K.W., Aboutajeddine, A., 2005. Forming limit comparison for FCC and BCC sheets, International Journal of Plasticity, 21, 1255?1266]. These authors performed their simulations based on a generalized Taylor-type polycrystal model (MK-FC), finding a remarkably low forming-limit curve for the FCC material and an extremely high forming-limit curve for the BCC material, in the biaxial stretching range. We verified that our predictions are similar to Inal?s results for both FCC and BCC materials when the MK-FC model is used. However, MK-VPSC calculations do not give such extreme values, and we believe that this theory predicts much more reliable results for both FCC and BCC crystallographic assumptions. We also found that localized necking depends on texture evolution in the vicinity of equi-biaxial stretching, through the sharpness of the predicted yield surface. Finally, it is shown that the MK-VPSC?s predictions are in good agreement with experimental data for AA5182- O and a DQ-type steel-sheet metal.